GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2018)
A dataset containing 54564 species occurrences available in GBIF matching the query: TaxonKey: Dactylorhiza fuchsii (Druce) Soó. The dataset includes 54564 records from 256 constituent datasets: 2 records from Floristic records in the Moscow and Novgorod regions. 2 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 17 records from Phase 2 Lowland Peatland Survey of Wales 2004 onwards. 14 records from National System of Protected Areas in Poland - Plants. 12 records from Species within North Ayrshire from 1984 - Present. 1 records from Schwanseepark (87645 Schwangau). 1 records from Australia's Virtual Herbarium. 1 records from Flora exsiccata Bavarica. 48 records from National Trust for Scotland Species Records. 1 records from BioFresh Pond Data. 4 records from NCC Berkshire Chalk Grassland Survey 1985. 23 records from Inventaire National du Patrimoine Naturel : Flore du Massif Armoricain. 24 records from Lund Botanical Museum (LD). 13 records from Ecofact. 21 records from Herbarium Senckenbergianum (FR). 193 records from Vascular Plant Herbarium, UiB. 19 records from Standing Waters Database - Scotland. 1406 records from naturgucker. 1 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Briof. 934 records from SEWBReC Vascular Plants (South East Wales). 35 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from GEO Hauptveranstaltung Tirol (Innsbruck). 283 records from BRERC species records within last 15 years. 97 records from Isle of Man historical wildlife records 1995 to 1999. 6 records from Welsh Invertebrate Database (WID). 122 records from Commissioned surveys and staff surveys and reports for Scottish Wildlife Trust reserves - Verified data. 49 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 154 records from A grid-based database on vascular plant distribution in Vladimir Oblast, Russia. 1 records from NINA botanical collection. 27 records from Hatfield Forest species data held by The National Trust.. 2 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 207 records from Distribution of Higher Plants in Greater Manchester. 1 records from Hoher Stein Kallenhardt. 92 records from iNaturalist Research-grade Observations. 1 records from Herbier de Strasbourg. 1 records from City of Edinburgh Natural Heritage Service - Historical Records. 24 records from Natural History Museum (London) Collection Specimens. 4 records from SysTax - Botanical Gardens. 2 records from Herbarium specimens of CBNA (GAP). 70 records from Estonian Nature Observations Database. 98 records from All taxa records for Leicestershire and Rutland between 1987 and 2016. 1 records from Finnish Floristic Database (Literature Sources). 19 records from NCC Berkshire Grassland Survey 1984-1987. 13 records from Wicken Fen nature reserve species data held by The National Trust. 5 records from Staatliches Museum für Naturkunde Stuttgart, Herbarium. 1 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 259 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 1 records from MBM - Herbário do Museu Botânico Municipal. 22 records from Carnet en Ligne. 1 records from SANT Herbarium vascular plants collection. 1 records from Jardín Botánico de Córdoba: Herbarium COA. 20 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Verified data. 1 records from National Plant Monitoring Scheme - Northern Ireland. 2 records from River Macrophytes Database. 1 records from Naturparadies in Gräfenhausen am Trifels (bei Annweiler). 3 records from Institut Botanic de Barcelona, BC. 222 records from Hertfordshire Flora Survey Records 1987-2005. 43 records from Ireland's BioBlitz. 1 records from Willersalpe. 116 records from Isle of Man wildlife records from 01/01/2000 to 13/02/2017. 5 records from Vascular Plants, Museum of Archaeology, University of Stavanger. 6 records from Merseyside BioBank Active Naturalists (unverified). 775 records from Environmental Monitoring Database Species data 1987 to 2015. 159 records from Online Atlas of vascular plants 2012-2020. 2 records from Biodiversitätsdatenbank des Landes Salzburg. 53 records from National Plant Monitoring Scheme - England, Scotland, Wales. 22 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 3 records from EURISCO, The European Genetic Resources Search Catalogue. 261 records from Finnish Floristic Database (Finnish Museum of Natural History Collections). 16 records from Natural History Museum, Vienna - Herbarium W. 6 records from Wimpole Estate species data held by The National Trust. 77 records from Natural History Museum, University of Tartu. 15 records from ArtenFinder. 1 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 3 records from Herbarium specimens of Limoges university (LIMO). 1 records from nazza. 37 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 50 records from Flore de Franche-Comté. 1 records from Records for Fife Nature Records Centre (Additional). 822 records from Gloucestershire Historic Wildlife Sightings prior to 1st Jan 2000. 1 records from Universidad Politécnica de Madrid, Dpto. Biología Vegetal, Banco de Germoplasma. 182 records from Floristic Databases of Mecklenburg-Pomerania - Higher Plants. 31 records from Merseyside BioBank (unverified). 4646 records from Other BSBI Scottish data up to 2012. 6 records from Anglesey Abbey wildlife species data held by The National Trust.. 4 records from Digitization of plant specimens from Rhoen and Vogelsberg (FULD). 3 records from Digitization of plant specimens from Rhoen and Vogelsberg (FLAD). 1 records from KU Grensestasjon nord Sør-Varanger 2013 - Vegetasjon. 59 records from CBDC: Cumbria Wildlife Trust: survey records from 1970 - 2007 of County Wildlife Sites.. 38 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 6 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 15 records from InboVeg - NICHE-Vlaanderen groundwater related vegetation relevés for Flanders, Belgium. 1 records from Artenvielfalt am Schlern. 2 records from Ty Canol National Nature Reserve (NNR) Species Inventory. 1 records from Species plots from the Norwegian Vegetation Mapping Programme. 295 records from Phanerogamic Botanical Collections (S). 149 records from Atlas Flora Danica. 235 records from Vascular plant field notes, NTNU University Museum. 1 records from Wildlife Observations Bardon Hill 31.5.09. 108 records from Dorset Sites of Nature Conservation Interest (SNCI) species records 2000-2008. 11 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 1 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 201 records from BioFokus. 1626 records from Waarnemingen.be - Plant occurrences in Flanders and the Brussels Capital Region, Belgium. 138 records from NRW Regional Data: all taxa (excluding sensitive species), West Wales. 296 records from Phase 2 Lowland Grassland Survey of Wales. 1 records from MGC Herbarium of University of Malaga (Spain): MGC-Cormof dataset. 9 records from Flora d'Andorra. 1 records from Ecological surveys from Bardon Hill undertaken in the period 2000 to 2007. 904 records from Shropshire Ecological Data Network database. 64 records from Herbarium BSG Vascular Plants. 4 records from Geographically tagged INSDC sequences. 80 records from National Wetland Inventory (NV). 121 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 10 records from Inventaire National du Patrimoine Naturel : Flore d'Ille-et-Vilaine. 19 records from Nature Conservancy Council Berkshire Meadows Survey 1984-87 (as held by Thames Valley Environmental Records Centre). 1 records from Alter Kreidebruch Saßnitz/Rügen. 616 records from Vascular plant herbarium, NTNU University Museum. 196 records from CSIC-Real Jardín Botánico-Anthos. Sistema de Información de las Plantas de España. 66 records from Herbarium of the Department of Natural Forests (Forest Research Institute) - Plants. 1359 records from Vascular Plant Herbarium, Oslo (O). 80 records from Local Wildlife Site Surveys Oxfordshire. 14 records from English Nature and NCC Oxfordshire Surveys. 79 records from Data from Defra Family Organisations supplied to Staffordshire Ecological Record. 5 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 1 records from City of Edinburgh Natural Heritage Service - Burdiehouse Burn Valley Park Wildflower Meadow Survey. 16 records from Flora of Słowiński National Park, Poland. 1 records from Herbarium of Namur. 1 records from KU E16 Slæn - Tvinno. 1 records from Miscellaneous Vascular Plants. 619 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 49 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 1 records from Promberg1. 2 records from Stoke-on-Trent Environmental Survey results (1982-1984). 65 records from TWIC Biodiversity Field Trip Data (1995-2014). 3 records from Plant observations from Białowieża National Park. 452 records from SER Site-based Surveys. 346 records from Vascular Plant Records up to 2010. 5 records from English Nature Grassland Survey 1995. 2 records from Liether Kalkgrube. 1 records from Warnowtal (Rostock). 1 records from English Nature Oxford City Surveys. 48 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 15 records from English Nature Oxfordshire Chalk Grassland Survey. 180 records from Dutch Vegetation Database (LVD). 5 records from RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 326 records from Rotherham Biological Records Centre - Non-sensitive Records from all taxonomic groups. 127 records from Jordal. 12 records from WTSWW Data: All Taxa (West Wales). 558 records from Moscow University Herbarium (MW). 8 records from Atlas des plantes vasculaires de Lorraine. 151 records from Estonian University of Life Sciences. 52 records from LNHG Biological Records Dataset. 2 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 8 records from Faun. 2096 records from Flora von Deutschland (Phanerogamen). 1 records from English Nature Oxfordshire Fen Survey 1990-1991 (A Comparative Survey of Rich Calcareous Fens of Oxfordshire) (as held by Thames Valley Environmental Records Centre). 320 records from National Trust Species Records. 8 records from Botany registration database by Danish botanists. 234 records from Flora of the Stołowe Mts.. 92 records from IBF Monitoring of Vascular Plants. 133 records from SER Species-based Surveys. 1 records from Wildwatch North Pennines AONB project records for Cumbria. 8 records from PlutoF platform observations. 10 records from Vegetation surveys of coastal shingle in Great Britain. 21 records from Tiroler Landesmuseum Ferdinandeum. 685 records from Natural Resources Wales Regional Data : Mid-Wales. 2 records from Herbario de la Universidad de Sevilla. 305 records from Wikiplantbase #Toscana. 2 records from City of Edinburgh Natural Heritage Service - Ranger Ad-hoc records and sightings. 1 records from Schlern - (Bozen). 63 records from Dataflos. 1 records from VegetWeb - Repositorium von Vegetationsaufnahmen a. 173 records from Données ONF Faune-Flore-FOnge. 2 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 1 records from Lothian Wildlife Information Centre Secret Garden Survey. 44 records from CSIC-Real Jardín Botánico-Colección de Plantas Vasculares (MA). 139 records from Royal Botanic Garden Edinburgh Herbarium (E). 1 records from Field Study Group of the Dutch Mammal Society (NL) - 2010 - Mammal Survey Patvinsuo National Park, northern Karelia, Finland. 58 records from NBIS Records to December 2016. 1 records from Merseyside BioBank Active Naturalists (verified). 5 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 169 records from Isle of Man historical wildlife records 1990 to 1994. 1 records from Artenvielfalt auf der Weide - GEO-Hauptveranstaltung in Crawinkel. 2 records from Vascular Herbarium, NMBU. 48 records from Inventaire National du Patrimoine Naturel : Flore Franco-Belge. 792 records from Flora of Worcestershire. 375 records from Miscellaneous records held on the Cofnod database. 424 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 111 records from Karplanter i vernet barskog og edelløvskog. 173 records from Données ONF Faune-Flore-Fonge. 25 records from Hatikka Observation Database. 128 records from Dorset SSSI Species Records 1952 - 2004 (Natural England). 173 records from Données ONF Faune-Flore-FOnge. 2 records from Living Collection of the Gothenburg Botanical Garden. 11 records from Herbarium specimens of the Muséum d'Histoire Naturelle of Aix-en-Provence (AIX). 106 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 2 records from English Nature Berkshire Staff Surveys 1990's. 740 records from Welsh BSBI data (ex-VPDB dataset) at hectad resolution. 5 records from Shire Group IDB species data 2004 to present. 34 records from Collections and observation data National Museum of Natural History Luxembourg. 264 records from The Changing Flora of Glasgow: Orchid Dataset. 1754 records from Norwegian Species Observation Service. 9 records from ARKO kulturmarkseng. 520 records from BRERC species records recorded over 15 years ago. 16 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 9 records from BBOWT Local Wildlife Sites Surveys 1994-2003. 737 records from Vascular Plants, Field notes, Oslo (O). 8 records from Natural History Museum Maastricht (NL) - Herbarium. 1527 records from Scottish SNH-funded BSBI records. 12 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 10 records from East Ayrshire Species Database. 3 records from Belgian IFBL Flora Checklists (1939-1971). 3 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 8189 records from INPN - Données flore des CBN agrégées par la FCBN. 1 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 2 records from Tropicos Specimen Data. 397 records from Naturalis Biodiversity Center (NL) - Botany. 1 records from Local BioBlitz Challenge 2013. 2 records from PlutoF platform reference-based occurrences. 16 records from NMNH Extant Specimen Records. 598 records from RECORD Vascular Plant Data. 12 records from A grid-based database on vascular plant distribution in the Meshchera National Park, Vladimir Oblast, Russia. 18 records from Phase Two Lowland Heathland Survey. 343 records from Vascular plant herbarium, Tromsø Museum. 1 records from Biologiezentrum Linz. 3 records from Species found in the NOMS estate 2005 - Present. 22 records from Botany (UPS). 2103 records from LERN Records. 2 records from University of Vienna, Institute for Botany - Herbarium WU. 5 records from Rådgivende Biologer. 33 records from Herbarium Senckenbergianum Görlitz (GLM). 9 records from Nature Conservancy Council Oxfordshire Fen Survey 1983 (as held by Thames Valley Environmental Records Centre). 1466 records from Occurrence Data of Vascular Plants collected or compiled for the Flora of Bavaria. 3 records from Tallinn Botanic Garden. 304 records from Observations du Conservatoire botanique national du Bassin parisien.. 1060 records from Vascular plants in power line clearings and the nearby forest, southeast Norway. 3 records from Casual records for Scottish Wildlife Trust reserves - Verified data. 161 records from Estonian Museum of Natural History. 36 records from Local Wildlife Site Surveys Berkshire. 1 records from Herbario de la Universidad Pública de Navarra, Pamplona: UPNA-H. 9 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 1 records from Vegetation data from phytosociological studies of the forests on the Fosen peninsula. 94 records from Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups. 4921 records from Artportalen (Swedish Species Observation System). 1 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 225 records from Merseyside BioBank (verified). 3 records from Observational database of Icelandic plants. 33 records from Oskarshamn herbarium (OHN). 5 records from Ickworth Estate species data held by The National Trust. 1 records from TransForest vegetation data. 12 records from Herbarium Berolinense. 1 records from EDIT - ATBI in Mercantour/Alpi Marittime (France/Italy). 58 records from NRW Regional Data: North Wales. 2 records from English Nature Berkshire SSSI Records. 1 records from NSG Karwendel. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences